Cooling and annealing of plastic pipe. (1st October 2021) - Poungthong, P.; Kolitawong, C.; Giacomin, A.J.
Abstract: In commercial pipe extrusion, when plastic pipe is extruded, the extrudate emerges from an annular die as hot molten plastic. The extrudate must be quenched suddenly and then solidified in a quench tank. Because of rapid quenching and large temperature differences between the inner and outer walls, one may need to release residual stress at the outer pipe surface to ensure pipe standard specification and stability over time. In this paper, for saving the extra cost and time, we present a new idea for plastic pipe manufacture that to release residual stress without annealing. The residual stress is calculated from a modified Jansen's model. To analyze this problem, we begin with the energy balance in Cartesian coordinates, and then nondimensionalize it. We propose a cooling temperature profile as a function of the pipe thickness and the cooling time. We next solve the dimensionless energy balances, in both cooling after solidification and annealing, for the times and temperature profiles of the pipe. We then validate our result with the measurement of a SDR 11 blue PE80 medium density polyethylene (MDPE) pipe. Our results help plastic engineers calculate the cooling time for both cases and to develop this extrusion line. Worked examples show how to use our results with and without annealing. By follow our suggestion, for high-density polyethylene (HDPE), the engineer can reduce production time up to three-fold over conventional manufacture.